Process development stabilized, spray-dried, whole egg powder - Alviar, Ma. Salome B. (1980)
The main objective of this study was to determine the feasibility of producing in the Philippines by spray-drying a stabilized, whole egg powder. The stepwise process studied was composed of the fermentation , pasteurization and the actual spray-drying process. The process developed includes the fermentation of the egg pulp for two hours with the temperature maintained at 30-32°C and 0.15% (by weight) of the yeast added. The fermented egg pulp is then pasteurized for 7 minutes at 62°C-63°C afterwhich it is filtered and fed immediately into the co-current flow laboratory spray-dried (Can.Pat.No.380, 431) with the chamber temperature maintained at 181-200°F. The cooked product prepared using the powder produced from developed process was inferior quality when compared with cooked, fresh scrambled eggs. However, further improvements can still be made on the powder so that it will simulate fresh scrambled eggs, in terms of color, flavor, and texture of the cooked fo